The Reflection of the Organization of Turkic States on the Russian Press - Erkan, Türker; Nergiz, Cebrail (Fırat University, 2024)
With the collapse of the Soviet Union in 1991, Turkic Republics gained their independence. States with common history and origins needed strong cooperation in military, diplomatic, economic, security and political fields in order to maintain their independence and increase their power. In this context, states of Turkic origin have expanded their cooperation by carrying out activities in many different fields under the name of "Heads of State of Turkic Speaking Countries" in 1992, "Turkic Council" in 2009 and "Organization of Turkic States" in 2021. The fact that the area of activity of the Organization of Turkic States is located in the same geography with the Russian Federation and that the organization is in close relations with its main member Turkey in many international fields is decisive in the activities of the organization. Based on this, this study aims to examine the presentation of the news about the Organization of the Turkic States on the leading news websites of the Russian media. In this context, news about the "Organization of Turkic States" published in Russia's top three leading news sites, "Gazeta.ru", "rbc.ru" and "russian.rt.com" internet newspapers between 2021 and 2023, were examined. Content analysis technique was used as a method in the study. The news was evaluated using categorical analysis and frequency analysis techniques. The study is important in terms of revealing the Russian press's view of the Organization of Turkic States.

Sovyetler Birliği’nin 1991 yılında dağılmasıyla birlikte Türki Cumhuriyetler bağımsızlıklarını kazanmıştır. Ortak tarih ve kökenden gelen devletlerin bağımsızlıklarını sürdürebilmeleri ve güçlerini artırabilmeleri için askeri, diplomatik, ekonomik, güvenlik ve siyasi alanlarda güçlü işbirliklerine ihtiyaç duymuşlardır. Bu kapsamda Türk kökenli devletler, 1992 yılında “Türk Dili Konuşan Ülkeler Devlet Başkanları,” 2009 yılında “Türk Konseyi” ve 2021 yılında ise “Türk Devletler Teşkilatı” adı altında farklı birçok alanda faaliyetlerde bulunarak iş birliklerini genişletmişlerdir. Türk Devletler Teşkilatı faaliyet alanının, Rusya Federasyonu ile aynı coğrafyada bulunması ve teşkilatın başat üyesi Türkiye ile Uluslararası birçok alanda yakın ilişki içerisinde olması teşkilatın faaliyetlerinde belirleyici olmaktadır. Buradan yola çıkan çalışma, Türk Devletler Teşkilatı haberlerinin Rus medyasının önde gelen haber sitelerinde sunum biçimlerini incelemek amacıyla ortaya konmuştur. Bu kapsamda Rusya’nın önde gelen ilk üç haber sitesi olan “Gazeta.ru”, “rbc.ru” ve “russian.rt.com” internet gazetelerinde 2021-2023 yılları arası “Türk Devletler Teşkilatı” ile alakalı çıkan haberler incelenmiştir. Çalışmada yöntem olarak içerik analizi tekniğinden yararlanılmıştır. Haberler, kategorisel analiz ve frekans analiz tekniği ile değerlendirmeye tabi tutulmuştur. Çalışma, Rusya basınının Türk Devletler Teşkilatına bakışını ortaya koyması açısından önem arz etmektedir.
TÜRK DEVLETLER TEŞKİLATININ RUS BASININA YANSIMASI
Keywords: Screen and Media Culture; Ekran ve Medya Kültürü